Capital flows to developing countries: Is there an allocation puzzle? - Josef Schroth (Bank of Canada, 2016)
Foreign direct investment inflows are positively related to growth across developing countries - but so are savings in excess of investment. I develop an explanation for this well-established puzzle by focusing on the limited availability of consumer credit in developing countries together with general equilibrium effects. In my model, fastgrowing developing countries increase their holdings of safe assets, which creates net capital outflows despite inflows of foreign direct investment. The world risk-free interest rate falls as a result, and slow-growing developing countries reduce their holdings of safe assets, which creates net capital inflows despite outflows of foreign direct investment.
Keywords: E13; E21; F43; 330; Foreign reserves management; Interest rates; International financial markets